Capacity management requirements for virtual enterprises - Abailardo Moreira (2003)
Transformations in the marketplace have led manufacturing companies to focus on their core competences and compete through new forms of enterprise partnerships. A new concept of enterprise partnership is that of Virtual Enterprise wherein autonomous or independent companies come together to temporally address a specific market demand, by collaborating closely and presenting to the market as a single enterprise. A number of traditional operations management models or techniques need to be redesigned in order to cope with the demands brought by the implementation of the Virtual Enterprise concept. This paper attempts to ascertain the understanding that exist about the concept of Virtual Enterprise as well as its associated managerial challenges. Then, focusing on the issues of manufacturing capacity management, the requirements for an effective deployment of this function in a Virtual enterprise environment are described.